A new species of leucosiid crab (Decapoda: Brachyura: Leucosiidae) from the Arabian Gulf - Giraldes, Bruno Welter; Al-Maslamani, Ibrahim; Smyth, David (Zootaxa, 2017)
The Indo-West Pacific genus Coleusia Galil 2006, was recently described and now comprises seven species. We describe a new species from the western Arabian Gulf, Coleusia janani n. sp. The new species is closely related to the congener C. biannulata (Tyndale-Biscoe & George, 1962), and can be distinguished from other species at these genus congeners mainly by the straight upward apical shape of the male first pleopod (G1). An updated identification key to the species of Coleusia, as well as an overview of the geographical distribution of the species included in the genus are also presented.